Design Ergonomic of Low-Energy Housing In Urban Housing Development - Khoirul Hidayat,M Adhi Prasnowo,Ernin Niswatul Ukhwah (International Conference on Industrial Revolution for Polytechnic Education, 2019)
The energy needs of each urban household are increasing, as the majority of urban household appliances use electrical energy, for example for lighting, air conditioning, refrigeration, washing, and cooking. Therefore it is necessary to research the ergonomic design of low-energy housing in urban housing development. This research uses Quality Function Deployment method to determine urban community needs in the low-energy housing design and determine its technical requirement and to produce three alternative design low-energy housing, then in choosing the best alternative of design low-energy housing using binary dominance matrix method. The result of the research shows that there are seven technical requirements; use of environmentally friendly materials, material cost, material availability, ease of manufacture, completion time, area, and home form architecture resulting in three alternative designs, alternate 1, alternative 2, and alternative 3. By using binary dominance matrix, it can be concluded that the design alternative 2 is the best alternative of design low-energy housing with a value of 7.16 and can save costs 55%.